DESAIN ORGANISASI DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN BANDUNG BARAT - Kartika Asri, Tika (Sekolah Tinggi Ilmu Ekonomi Dewantara, 2019)
This research aims to determine how the organizational design of Department of Transportation, Communication and Information in West Bandung Regency. Hellriegel and Slocum, there are have six elements such as task, technology, strategic, design, culture, and people. The researcher using qualitative methods with collection of data technique by library research, observation and interview. Informants on this research were selected based on purposive technique with sampling data and consideration. Data analysis is start from data reduction, data presentation, and conclusions. The results implementation of organizational design at Department of Transportation, Communication and Information in West Bandung Regency yet optimally, because there’s some aspects that have not been fulfilled. The problem solving from the researcher is restructure the design organization at Department of Transportation, Communication and Information in West Bandung Regency. Government have to consideration to merge between transportation field with communication and information filed, cause both of them have different function, role and job to achieve the purpose in West Bandung Regency.